A new proposal for the Bilbilis-Numancia road as a strategic junction between route XXV and XXVII (Salduie, 2023)
The study carried on the historic road of Pomer has allowed us to propose that at least the origin of the old road, as well as some visible remains, could actually be in the sought after Bilbilis-Numancia road, traditionally associated with the route of the N-234. We present a state of the art updated with those formulated by other authors, as well as the toponymic, hodomonymic, documentary, cartographic, geographical and archaeological sources on which we base our proposal. The analysis of all of them makes us propose that the passage of the road was diverted in Clarés de Ribota towards Masegoso, passing through Pomer and Borobia, and that in reality it constitutes a junction between the itineraries XXVII – Caesaraugusta-Asturica and XXV – Caesaraugusta-Emerita Augusta.
Keywords: Roman road; Moncayo; Celtiberia; Romanization; Toponymic studies